2009
DOI: 10.1016/j.vph.2009.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Exercise increases the phenylephrine effects in isolated portal vein of trained rats

Abstract: Physical exercise evokes an extensive circulatory redistribution. However, the influence of exercise upon the effects of sympathomimetic agonists in veins was not well studied. Thus, the present study aimed to determine whether a single bout of exercise modifies the effects of sympathomimetic agonists in veins and whether this exercise-induced modification may be altered by exercise training. The results have shown that the training did not change the responsiveness of the rat portal vein, but exposure of trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The results of the present study indicate that ET, through both ET A and ET B receptors, mediates the increase in the R max to PE in the rat portal vein following orchidectomy. Previously, we reported indirect evidence that ET, through either ET A or ET B receptors, contracts the rat portal vein 27 . Other studies suggest that ET released from the rat portal vein endothelium has a potent venoconstrictor effect on the venous bed through ET A and/or ET B receptors 51–53 .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The results of the present study indicate that ET, through both ET A and ET B receptors, mediates the increase in the R max to PE in the rat portal vein following orchidectomy. Previously, we reported indirect evidence that ET, through either ET A or ET B receptors, contracts the rat portal vein 27 . Other studies suggest that ET released from the rat portal vein endothelium has a potent venoconstrictor effect on the venous bed through ET A and/or ET B receptors 51–53 .…”
Section: Discussionmentioning
confidence: 79%
“…However, the venous bed stores 60–80% of the blood of mammals during rest 24,25 and large blood volumes must be shifted from this vascular compartment towards the heart to ensure ideal cardiac output 26 . Previously, we proposed that changes in the responsiveness of the portal vein, but not the vena cava, may be essential to circulatory redistribution in situations such as physical exercise 27 . To expand our understanding of the effects of testosterone on the vascular bed, in the present study we investigated the effects of testosterone on the portal vein and vena cava, which drain blood from the splanchnic and musculocutaneous territories, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the venous bed, such exercise-induced adaptations may assume different features depending on territory. For example, Ang II responses are changed by exercise exposition in the portal vein, but not in the vena cava [6]. It was also observed that a single bout of exercise, as well as exercise http://dx.doi.org/10.1016/j.peptides.2016.12.013 0196-9781/© 2016 Elsevier Inc. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, these heterogeneous responses may also be due to differences in the distribution of adrenoceptors. In fact, α 1 -adrenoceptors are expressed in many venous segments such as portal vein [9,10] and vena cava [11][12][13], which evoke vasoconstriction when stimulated. However, the α 1 -adrenoceptor expression appears not to occur in the jugular vein [14].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the modulation exerted by locally produced substances, such as nitric oxide (NO) and prostanoids, may influence the effects of both NE and PE in these veins, thereby disclosing this difference of responses. Indeed, NO and prostanoids may modulate effects of sympathetic agonists on veins [10,27].…”
Section: Introductionmentioning
confidence: 99%